Ab initio calculations on low-lying electronic states of SiH+. (December 2018) - Biglari, Zeinab; Shayesteh, Alireza; Ershadifar, Shokouh
Highlights: We have calculated several electronic states of SiH + at the MRCI level of theory. Scalar relativistic and spin-orbit corrections were included in our calculations. Transition dipole moments and lifetimes were computed for several excited states. SiH + might be found in interstellar clouds. Abstract: Ab initio potential energy curves have been calculated for the ground and low-lying excited electronic states of SiH + including the X 1 Σ +, A 1 Π, 1 1 Δ, 2 1 Σ +, 2 1 Π, 3 1 Σ +, 3 1 Π, 2 1 Δ, 4 1 Σ +, a 3 Π, 1 3 Σ −, 1 3 Σ +, 2 3 Π, 3 3 Π, 2 3 Σ −, 2 3 Σ +, 3 3 Π, 1 3 Δ, 1 5 Σ − and 1 5 Π states. The calculations were carried out at the multi-reference configuration interaction level including the scalar-relativistic effects. The computed transition dipole moments were used to calculate Einstein A coefficients for the spin-allowed transitions and the lifetimes for bound vibrational levels of the excited states. In addition, spin-orbit calculations were carried out to compute radiative lifetimes for the spin-forbidden a 3 Π → X 1 Σ + transition, and to predict local perturbations between the 2 3 Π and 1 1 Δ states due to off-diagonal spin-orbit matrix elements. Graphical abstract: